2013
DOI: 10.5194/hess-17-947-2013
|View full text |Cite
|
Sign up to set email alerts
|

A model of hydrological and mechanical feedbacks of preferential fissure flow in a slow-moving landslide

Abstract: Abstract. The importance of hydrological processes for landslide activity is generally accepted. However, the relationship between precipitation, hydrological responses and movement is not straightforward. Groundwater recharge is mostly controlled by the hydrological material properties and the structure (e.g., layering, preferential flow paths such as fissures) of the unsaturated zone. In slow-moving landslides, differential displacements caused by the bedrock structure complicate the hydrological regime due … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Wetting/drying cycles are considered important in cracking, even in deep-seated failure movements and despite the fact that preferential flow paths will only influence the soil mantle 52 . It has also been shown that soil swelling, continuous opening/closing of the fissures, and compaction/compression forces of upslope material will result in increased pore-fluid pressure and thereby act as important drivers of activity in clay-rich, slow moving earthflows 10,53,54 . Despite the fact that forested slopes are somewhat less susceptible to occurrence of desiccation cracks than bare surfaces, the enlargement of tension cracks (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Wetting/drying cycles are considered important in cracking, even in deep-seated failure movements and despite the fact that preferential flow paths will only influence the soil mantle 52 . It has also been shown that soil swelling, continuous opening/closing of the fissures, and compaction/compression forces of upslope material will result in increased pore-fluid pressure and thereby act as important drivers of activity in clay-rich, slow moving earthflows 10,53,54 . Despite the fact that forested slopes are somewhat less susceptible to occurrence of desiccation cracks than bare surfaces, the enlargement of tension cracks (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It will be both illuminating and important to continue to monitor these earthflows as rainfall returns, particularly given the hypothesis that extreme drying may increase pathways for runoff into earthflows through development of cracks [Krzeminska et al, 2013;McSaveney and Griffiths, 1987]. Catastrophic failure of earthflows is not common but the current extreme drought may generate an unprecedented, nonlinear response [Pelletier et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors recognized the role of discontinuities as preferential flow paths that facilitate the propagation of pore water pressure associated to rain (among others, [4−8]). The influence of discontinuities on landslide behavior was also discussed by Hencher [9], Sharma & Nakagawa [10], and Krzerminska et al [11], for a two-fold mechanism: faster pressure build-up and enhanced drainage. Vitone and Cotecchia [12] and Cotecchia et al [13] considered fissures as an internal factor predisposing the slope failure from both mechanical and hydraulic points of view.…”
Section: Introductionmentioning
confidence: 87%